SINERGI SUPPLY CHAIN YANG EFEKTIF : LITERATURE REVIEW AGROINDUSTRI BAWANG MERAH DI SUMATERA BARAT - Dedet Deperiky, Santosa, Rika Ampuh Hadiguna, Nofialdi (Jurnal Teknologi Industri Pertanian, 2019)
The agroindustry of shallot in West Sumatra currently requires further strengthening of therelationship between supply chain actors to improve the efficiency of the market system and the application of modern technology today. This study aims to photograph the supply chain of shallot agroindustry in West Sumatra and reconstruct the synergy of shallot agroindustry supply chain actors for the welfare of farmers. The research methodology used to Systematic Literature Review (SLR), methode that is literature review method which identify, assess, and interpret all findings on a research topic, to answer research question.The results of the study that the portrait of shallot agroindustry supply chain is mapping the market potential that is a mainstay in shallot agroindustry, conducting comparative analysis of the role of stakeholders in the supply chain as a business unit, mapping gaps in profit distribution among supply chain actors and accrue recorded price data. Farmers and has a high ability in market access and integrated in all business processes with all supply chain stakeholders. In conclusion, synergiof supply chain on integrated shallot agroindustry will correlated to the increasing ability of the resourches supply chain shallot agents of agroindustry from various elements and to integrate a more efficient and effective supply chain that transforms the agricultural sector into the industrial sector.Keywords: supply chain, agroindustry, synergi, agriculture sector